Spinal arteriovenous shunts: Accuracy of shunt detection, localization, and subtype discrimination using spinal magnetic resonance angiography and manual contrast injection using a syringe - Kittisak Unsrisong (2018)
©AANS, 2016. OBJECT: The object of this study was to evaluate the accuracy of fast 3D contrast-enhanced spinal MR angiography (MRA) using a manual syringe contrast injection technique for detecting and evaluating spinal arteriovenous shunts (AVSs). METHODS: This was a retrospective study of 15 patients and 20 spinal MRA and catheter angiography studies. The accuracy of using spinal MRA to detect spinal AVS, localize shunts, and discriminate the subtype and dominant arterial feeder of the AVS were studied. RESULTS: There were 14 pretherapeutic and 6 posttherapeutic follow-up spinal MRA and catheter spinal angiography studies. The spinal AVS was demonstrated in 17 of 20 studies. Spinal MRA demonstrated 100% sensitivity for detecting spinal AVS with no false-negative results. A 97% accuracy rate for AVS subtype discrimination and shunt level localization was achieved using this study's diagnostic criteria. The detection of the dominant arterial feeder was limited to 9 of these 17 cases (53%). CONCLUSIONS: The fast 3D contrast-enhanced MRA technique performed using manual syringe contrast injection can detect the presence of a spinal AVS, locate the shunt level, and discriminate AVS subtype in most cases, but is limited when detecting small arterial feeders.